Bidding Behavior in Treasury Bill Auctions : Evidence From Pakistan. (IMF Working Papers; Working Paper ;, 2000)
Behavior in the first three years of auctions for Pakistani treasury bills is studied. Bidding strategies rapidly converged to a consistent pattern after the auctions started in 1991. Factors are identified that influenced the expected profitability of auction participation, which was on average low and did not differ between types of bidders. Prices bid are found to reflected both 'buy and sell' and 'buy and hold' strategies, and were affected by risk considerations and bidder-specific variables. The Pakistani experience suggests the robustness of auctions as a market-based allocation mechanism, and their value in public debt management.